Effectiveness of STEM-Oriented Project-Based Learning Modules in Visual Communication Design to Support Science and Technology Skills in Vocational Education - Deliana; Muhammad Anwar (Postgraduate, University of Mataram, 2025)
This study aims to develop and evaluate the effectiveness of a STEM-oriented entrepreneurship-based learning module using a Project-Based Learning (PjBL) model in the Basic Principles of Design and Visual Communication subject at SMK Negeri 2 Guguak. The research used the Research and Development (R&D) method with the 4D model (Define, Design, Develop, Disseminate). Data were collected through observations, expert validations, and pretest-posttest experiments involving teachers and students. The module received high feasibility ratings from media experts (4.87) and material experts (4.89). Practicality tests showed very practical results from both teachers (97.38) and students (87.11). Effectiveness was confirmed through a Paired Samples Test with significant improvements in student learning outcomes (Sig < 0.005; t-value > t-table). In conclusion, the developed module is valid, practical, and effective in improving learning outcomes and integrating STEM-based competencies in vocational education.